Tracking the progress : alternative learning system passers readiness and experiences in entering the senior high school program - Vizcarra, Glenny C. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2023)
This mixed-method research study assessed and analyzed the level of readiness and experiences of the Alternative Learning System passers in entering the Senior high School program. Specifically, it determined the profile of the learners, level of readiness, difficulties encountered, and the adjustment strategies being practiced in overcoming the difficulties as a basis for formulating strategic bridging plan. A total of 64 ALS passers who are currently enrolled in senior high school served as the respondents of the study. A research-made questionnaire survey and an interview guide question served as data-gathering tools. The data gathered were treated statistically using frequency count, percentages, and ranks. The level of readiness of ALS passers along preparatory, self-efficacy, and academics is partially ready. the difficulties encountered were lack of financial support, lack of self-confidence, inadequate knowledge of academics. and poor time management. The adjustment strategies practiced by the respondents were effective time management, self-determination, and keeping a support system. The researcher recommended a strategic bridging plan to address the identified difficulties of the learners and to improve learning outcomes.
References: pages 113-117.
CHED-La Union
Keywords: Alternative learning system